Effectiveness of Islamic Religious Education in Developing Students’ Religious Character - Utep Sultan; Fitriyani Kosasih (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to analyze the effectiveness of Islamic Religious Education (IRE) in shaping students’ religious character at MTs An-Nur, Pacet District, Bandung Regency, as well as to identify the supporting and inhibiting factors in its implementation. The study is grounded in the recognition of IRE as a strategic instrument for fostering a generation that is faithful, pious, and of noble character amid the challenges of globalization, the influence of digital media, and shifting social values. The research employed a qualitative approach with a case study design. Research subjects included IRE teachers, the school principal, students, and parents, selected purposively. Data were collected through participant observation, in-depth interviews, and document analysis, and were analyzed using Miles, Huberman, and Saldaña’s interactive model, which comprises data reduction, data display, and conclusion drawing/verification. Data validity was ensured through source triangulation and member checking. The findings indicate that IRE at MTs An-Nur positively contributes to the development of students’ religious character through a curriculum that incorporates Islamic values, teacher role modeling, participatory learning strategies, and a supportive school environment. However, its effectiveness is hindered by the limited integration of religious values into daily life, the influence of social media and popular culture, and the lack of synergy between school, family, and community. The study recommends strategies to enhance the effectiveness of IRE through the integration of Islamic values across all subjects, continuous professional development for IRE teachers, multi-stakeholder collaboration, and the use of technology as a medium for character education.